Pathogenicity of birnaviruses isolated from turbot (Scophthalmus maximus): Comparison with reference serotypes of IPNV - Novoa, Beatriz; Rivas, Carmen; Toranzo, A. E.; Figueras Huerta, Antonio (Aquaculture, 1995)
8 páginas, 2 figuras, 2 tablas The pathogenicity of different bimavims strains to turbot was determined by challenge experiments. The reference strains of IPNV (Sp, Ab and VR-299) were not pathogenic for turbot (Scophthalmus maximus). The Norwegian serotype (Nl) and two selected bimavirus strains isolated from turbot and related to the Ab serotype of IPNV (TB-306 and TB-390) were virulent to different degrees for turbot and the virus could be recovered from survivor fish. Other turbot bimavirus strains (TB-3 11, TB-231,TB-160 andTB-460) werelessvirulentfor this species.Neutralizingantibodies weredetected with low titer in 30 g turbot inoculated with a virulent strain (TB-306). No pancreatic necrosis was found in turbot inoculated with this viral strain (TB-306)) but this lesion was present in inoculated rainbow trout (Oncorhynchus mykiss). This work was supported by Grant AGF-93-0769-C02-02 from the Comision Interministerial de Ciencia y Tecnologfa (CICYT) , Spain. Peer reviewed